Stage‐dependent effects of exogenous TRAIL on atherogenesis: role of ER stress‐mediated sensitization of macrophage apoptosis. (May 2016) - Liu, Fangfang; Cheng, Wen; Bi, Xiaolei; Zhang, Yun; Zhao, Yuxia; Jiang, Fan
Summary: Deletion of the gene of tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL) in apolipoprotein E‐deficient (ApoE−/−) mice increased atherosclerosis. However, the effect of TRAIL at a supra‐physiological level on early atherogenesis is unknown. ApoE−/− mice were divided into Early (high‐fat diet with concomitant TRAIL treatment for 4 weeks) and Late (high‐fat diet for 16 weeks with TRAIL being given during the last 4 weeks) groups. It was found that TRAIL stimulated atherogenesis in the Early group but not in the Late group. TRAIL did not change the intra‐plaque macrophage content in Early group, but decreased it in the Late group. In cultured macrophages, induction of endoplasmic reticulum (ER) stress increased death receptor 5 (DR5) expression and TRAIL‐induced apoptosis, which were mediated by the transcription factor CCAAT/enhancer‐binding protein homologous protein (CHOP). The expression levels of CHOP, 78 kDa glucose‐regulated protein (GRP78) and DR5 were all elevated in the Late group. TRAIL treatment in vivo also increased intra‐plaque apoptotic only in Late lesions. Moreover, the chemical chaperone 4‐phenylbutyrate blocked the development of ER stress and upregulation of DR5 in Late lesions in vivo . In conclusion, TRAIL at a supra‐physiological level has a stimulatory effect on early atherogenesis, but not in the advanced lesions. The differential effects of TRAIL may be related to differences in ER stress, DR5 expression, and the sensitivity of macrophage apoptosis in response to TRAIL in early versus advanced lesions. The results presented here raise the possibility that treatment with exogenous TRAIL as a therapeutic agent may be detrimental in patients with increased risk of atherosclerosis.